Improving Nutrition and Nutrition Education in the Burn Unit of a Developing Country: A Qualitative Study - Jonathan Bayuo; Joyce Pwavra; Jephtah Davids; Anita Eseenam Agbeko; Paa Ekow Hoyte-Williams; Frank Bediako Agyei; Pius Agbenorku (European Burn Journal)
Burn injuries can trigger a series of metabolic and catabolic responses that exert significant impacts on an individual’s nutritional status, necessitating continuous nutritional support and education to aid recovery. However, burn units in developing countries often face resource limitations that can negatively affect these needs. This study aimed to explore the challenges related to post-burn nutrition and nutrition education in our burn unit and identify ways to improve the situation. An interpretive description approach was used, and convenience sampling recruited fifty-three participants, including 18 adult burn survivors and their primary caregivers (each as a single dyad), 10 informal caregivers of paediatric burn survivors, and 25 burn care staff. The data were analysed through thematic analysis, revealing three main themes and seven subthemes. The findings highlight an unstructured approach to nutrition and education, along with financial constraints affecting adherence. To address these issues, strategies such as using educational materials like videos and booklets/leaflets in the local language are suggested to develop relevant interventions. In conclusion, while there are concerns about nutrition and education, there are also opportunities to improve the situation.